Ethnobotanical Inventory of Wild Woody Plants Species of Randyam Mountainous Zone of Bhimber, Azad Jammu and Kashmir Pakistan - Humaira Khanum; Ishtiaq, Muhammad; Tanvir Hussain; Mehwish Maqbool; Zil e Arooj; Syed Atiq Hussain; Mazhar, Muhammad Waqas (Ethnobotany Research and Applications, 2024)
Background: Traditional ethnobotanical knowledge (TEK) of wild tree plants (WTPs) of Randyam Mountainous Zone was collected to evaluate economic and medicinal uses with conservation perspectives for sustainable availability. Methods: This study was conducted in 2018-19 through interactions with indigenous communities. Open-ended and closed-ended interview protocols were employed to gather information. Microstatistical tools: informant consensus factor (ICF), relative frequency of citation (RFC), relative order of priority index (ROP) and use value index (UVI) were applied. Results: The ethnobotanical data of 21 WTPs from 9 families was collected through filed visits, plant interviews and community participation approach. The results indicated that the highest ICF was 0.91 for skin diseases. Azadirachta indica has FL value of 100% which is indicator of common popularity in the area. UVI of Azadirachta indica was 0.61 while RFC was 55. ROP of two trees: Acacia arabica and Azadirachta indica was the highest (100) which was indicator of their prevalent use in ethnomedicines in the study area. The research proved that Azadirachta indica has very common use in agriculture and also marketed on commercial scale. WTPs like Dalbergia sissoo, Pinus roxburghii and Senegalia modesta were used timber and fuel at domestic and commercial level. There is severe biotic pressure on many of the WTPs and there is need to work for their conservation and propagation. Conclusion: The research strongly recommends for taking immediate measures for protection and conservation of native WTPs of RMZ for sustainable natural resources to cope necessities of indigenous people and keep mitigating drastic impacts of climatic changes. Keywords: Traditional ethnobotanical knowledge; Preservation, Sustainable use of natural resources; Randyam Mountainous Zone.